CD19-directed CAR T cells as first salvage therapy for large B-cell lymphoma: towards a rational approach - Dreger, Peter; Corradini, Paolo; Gribben, John G.; Glaß, Bertram; Jerkeman, Mats; Kersten, Marie Jose; Morschhauser, Franck; Mussetti, Alberto; Viardot, Andreas; Zinzani, Pier Luigi; Sureda, Anna (The lancet. Haematology, 2023)
The approval of CD19-directed chimeric antigen receptor (CAR) T-cell therapies for the second-line treatment of high-risk large B-cell lymphoma (LBCL) has greatly affected salvage algorithms for this condition, and such therapies could have the potential to improve the course of relapsed or refractory LBCL. In this Review, we provide guidance for a rational management approach to the use of commercial CD19-directed CAR T cells in the second-line treatment of LBCL, addressing crucial questions regarding eligible histologies; age, comorbidity, and tumour biology restrictions; the handling of very aggressive tumour behaviour; and holding and bridging therapies. The guidance was developed in a structured manner and, for each question, consists of a description of the clinical issue, a summary of the evidence, the rationale for a practical management approach, and recommendations. These recommendations could help to decide on the optimal management of patients with relapsed or refractory LBCL who are considered for second-line CAR T-cell treatment.